Effect of Nanoparticles of Different Nature on the Adenosine Triphosphatase Activity of Azotobacter vinelandii IMV B-7076 and Bacillus subtilis IMV B-7023 - Chobotarov, A.Yu.; Chuiko, N.V.; Chobotarova, V.V.; Kurdish, I.K.; Чоботарьов, А.Ю.; Чуйко, Н.В.; Чоботарьова, В.В.; Курдиш, І.К. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
Under soil conditions, bacteria interact with nanoparticles of natural nanomaterials and ions. The study of such interaction and its effect on ATPase activity of bacteria is an important issue contributing to the understanding of the mechanisms underlying the functioning of living cells in their interaction with nanomaterials. Objective. To investigate ATPase activity of nitrogen-fixing and phosphate-mobilizing bacteria exposed to silica and bentonite nanoparticles and some ions. Methods. ATPase activity of the culture was determined by the concentration of phosphate in the reaction mixture. Silica and bentonite were used as effectors for ATPase activity determination. Results. The level of ATPase activity of Azotobacter vinelandii IMV B-7076 was shown to increase by 241 % after 48 hours of culturing and by 97 % after 72 hours of culturing compared to 24-hr culture. Magnesium and calcium cations were found to significantly increase ATPase activity of A. vinelandii and B. subtilis, whereas sodium and potassium ions had little effect on this process. Conclusions. The ATPase activity of Azotobacter vinelandii IMV B-7076 and Bacillus subtilis IMV B-7023 was found to be the highest in the presence of magnesium and calcium ions. The interaction of these strains with bentonite nanoparticles significantly stimulated the ATPase activity of the bacteria, while silica nanoparticles negatively affected the ATPase activity of A. vinelandii and positively affected that of B. subtilis.